(untitled) (Research, Society and Development, 2023)
The present study aims to describe the bacteriological profile of tracheal secretion in ICU patients, the mechanisms of bacterial resistance and the control of these bacteremias. This is a narrative review of the literature. The characteristic is that it is an exploratory and descriptive study. For which searches in international and national bibliography were used. The searches were carried out between the months of July and October 2023 in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MedLINE) and Scientific Electronic Library Online ( SciELO). Bacteremia that can occur in the respiratory tract and other systems has a high rate of damage. Due to the variety of possible resistance mechanisms, multiresistant bacteria or superbacteria end up causing a lot of damage, especially to people admitted to intensive care units. in addition to causing economic losses, given the high cost of treatment and length of stay. Knowing that induced resistance is one of the main resistance mechanisms, it is of utmost importance to maintain a rigorous standard of rational use of antibiotics at home and in hospitals, to reduce cases of resistance and control the spread of infections, to through education of care teams. , encouragement and awareness about the importance of hand hygiene.